Контактна задача для шару за врахування тертя - Soliar, O. I.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2024)
A numerical algorithm has been developed for solving a frictional contact problem concerning the interaction of a layer with punches of complex shapes. The algorithm is based on the application of the integral equation method and reduction to a quadratic programming problem. The kernels of the integral equations are derived using the fundamental solution for a layer, represented in a compact analytical form. The contact problem with an unknown contact region is formulated in terms of Signorini-type integral equations-inequalities. By employing cubature formulas, the problem is discretized into a system of linear algebraic equations-inequalities, which is subsequently transformed into a quadratic programming problem. The efficiency and applicability of the developed algorithm are demonstrated through the analysis of frictional contact interactions between the layer and punches of various shapes. Cite as: O. I. Soliar, Frictional contact problem for a layer,” Prykl. Probl. Mekh. Mat., Issue 22, 106-116 (2024) (in Ukrainian), https://doi.org/10.15407/apmm2024.22.106-116